2012
DOI: 10.1017/s095026881200132x
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella holmesiiin children suspected of pertussis in Argentina

Abstract: SUMMARYWe describe nine patients (eight aged <1 year) clinically diagnosed with pertussis yet laboratory-confirmed withBordetella holmesiiinfections, a human pathogen normally isolated from blood. Most patients reported cough and cold symptoms. No death was reported. We reportB. holmesiiisolation in infants with respiratory symptoms in Argentina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 11 publications
2
23
0
5
Order By: Relevance
“…This poses a potential problem, because the diagnosis of B. pertussis infection is based on the PCR detection of IS481 sequences. The development of specific PCR diagnosis for B. holmesii infection, targeting the recA gene [7][8][9], or the transposase IS1001bho [10], the amplification of specific target as bhoE [11] or the sequencing of 16sRNA or OmpA [12] has made it possible for a number of retrospective studies to demonstrate an increase in the number of reported cases of respiratory infections due to B. holmesii over the last few years [10,11,[13][14][15][16][17][18][19][20][21]. We wondered whether this increase in detection reflected a real increase in the number of infections or was simply a consequence of the increasing use of RT-PCR targeting IS481 for the diagnosis of B. pertussis since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…This poses a potential problem, because the diagnosis of B. pertussis infection is based on the PCR detection of IS481 sequences. The development of specific PCR diagnosis for B. holmesii infection, targeting the recA gene [7][8][9], or the transposase IS1001bho [10], the amplification of specific target as bhoE [11] or the sequencing of 16sRNA or OmpA [12] has made it possible for a number of retrospective studies to demonstrate an increase in the number of reported cases of respiratory infections due to B. holmesii over the last few years [10,11,[13][14][15][16][17][18][19][20][21]. We wondered whether this increase in detection reflected a real increase in the number of infections or was simply a consequence of the increasing use of RT-PCR targeting IS481 for the diagnosis of B. pertussis since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increase in number of notifications of pertussis observed in other countries (16,17) and also in Brazil, for over a decade, there was a need to implement a diagnostic method with higher sensitivity and specificity, with a shorter time to release results. Then, in 2010, we standardized the Real-Time PCR TaqMan® (RT-PCR) in routine diagnosis of Instituto Adolfo Lutz, the national reference center for pertussis in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important for adolescent and adult populations. As previously shown, B. holmesii carriage is mostly found in teenagers and adults, at least in Europe and North America (10,11), although it has been detected in some newborns in Romania, Chile, and Argentina (12)(13)(14). In these populations, it is important to identify the Bordetella species present in the samples, particularly when vaccine effectiveness or the duration of vaccineinduced immunity is determined.…”
mentioning
confidence: 99%